The Economic Burden of Providing Health Insurance How Much Worse Off Are Small Firms? - Eibner, Christine (RAND Corporation, 2008)
More than 60 percent of nonelderly Americans receive health-insurance (HI) coverage through employers. However, rising health-care costs may threaten the long-term viability of the employer-based insurance system. This report explores trends in the economic burden associated with HI provision for small and large businesses, as well as the quality of plans that small and large firms offer.